The Use of Autonomous Weapon Systems in Armed Conflict: Legality and Challenges for Future Weapon Regulation - Wilia, Andreas (Padjadjaran Journal of International Law, 2019)
AbstractAutonomous Weapon Systems (AWS) has been developed as an alternative weapon system in the battlefield. It has a fundamental difference with other weapon systems which lies in the decision making carried out without human intervention. AWS is able to take decisions about life and death and has been legally, morally and ethically challenged. However, as a smart weapon, it gives significant advantage since it can be deployed in very danger areas for human being in the battlefield for the purpose of self-defense in critical situation. This article argues that AWS is still a conventional weapon and its use cannot be absolutely prohibited even if it is deemed as a vulnerable and destructive weapon which potentially violates international humanitarian law (IHL). AWS can fully comply with IHL basic principles for as long as there is a sufficient legal basis that regulates the limit and legality of its use. Accordingly, as a ?modern? smart weapon, this article suggests that the future AWS regulation should be followed by appropriate technical provisions on the AWS? development, production, ownership, transfer and use in armed conflict.Keywords: Armed Conflict, Autonomous Weapon Systems, International Humanitarian Law, Weapon Regulation AbstrakSistem Senjata Otonom (AWS) telah dikembangkan sebagai sistem senjata alternatif dalam pertempuran dan memiliki perbedaan fundamental dengan sistem senjata lain yaitu, keputusan yang diambil tanpa adanya intervensi manusia. AWS mampu untuk memutuskan hidup dan matinya target kombatan sehingga penggunaannya ditentang bagik secara hukum, moral, dan etika karena berpotensi merusak moral dan etika dalam peperangan. Namun demikian, sebagai senjata modern, AWS memberikan keuntungan yang nyata mengingat AWS dapat ditempatkan di daerah yang berbahaya bagi manusia untuk alasan bela diri dalam situasi yang sangat sulit. Penelitian ini menyatakan bahwa AWS tetap merupakan senjata konvensional yang penggunaannya tidak dapat dilarang secara absolut sekalipun berpotensi menjadi senjata penghancur yang dapat melanggar hukum humaniter. AWS mampu untuk mematuhi prinsip-prinsip dasar hukum humaniter sepanjang pengaturan dan pembatasan penggunaannya diatur dalam instrumen hukum humaniter yang memadai yang hingga saat ini belum tersedia. Dengan demikian, penelitian ini menyarankan bahwa aturan AWS masa depan harus juga mencakup aturan-aturan teknis tentang pengembangan, pembuatan, kepemilikan, pengalihan serta penggunaan dari AWS dalam sengketa bersenjata.Kata Kunci: Aturan Senjata, Konflik Bersenjata, Hukum Humaniter Internasional, Sistem Senjata Otonom